KINEMATICS OF THE PROCESS OF AMMONIFICATION, NITRIFICATION, DENITRIFICATION - , Л. И., Т. А. (Municipal economy of cities. Series: «Economy science», 2013)
Considered depending on the kinematic processes remove nitrogen compounds from the main parameters of wastewater.